DAMPAK KEBIASAAN MEROKOK PADA ALOKASI PENGELUARAN SANTRI DI PONDOK PESANTREN: (Suatu Studi Kualitatif di Pondok Pesantren API Tegalrejo - Nakuloadi, Hening (PRIMA EKONOMIKA, 2021)
Tobacco is one of the components in cigarettes and is estimated to have killed more than six million people annually worldwide and is estimated to reach more than eight million by 2030. Household spending on tobacco and cigarettes is 63% of households in Indonesia. spending on cigarettes, it is known that household spending on buying tobacco or cigarettes in the poorest households is much higher than other important household expenditures such as education, health, eggs, milk and meat. in managing their finances in daily life. This study uses qualitative methods to explore the extent of understanding of the dangers of smoking, easy access to cigarettes, and daily expenses for buying cigarettes and the rules that exist in Islamic boarding schools. The informants used were, students who smoked under 17 years, students who smoked above 17 years, students who did not smoke, head of the room, boarding school administrators and boarding school caregivers. Data collection used observation and in-depth interviews, and the technique of collecting sources used purposive techniques. sampling while data analysis using content analysis. From the results of the study, it was found that Islamic boarding schools had published Islamic boarding schools as non-smoking areas, but students still violated the rules for various reasons, one of which was because they had been smoking since before at the boarding school, and the reason for supporting the learning process at the Islamic boarding school. The daily money arrangement is optimized to buy cigarettes, in addition to maintaining sleepiness as well as `being a social tool among students' friends. So sometimes the fulfillment of daily needs such as eating is defeated to buy cigarettes. Rules and punishments have been carried out every day, but their behavior still violates the smoking regulations in hidden places. It is recommended that there be a Multi-level Health Promotion Movement that supports and protects children's rights to be free from cigarette smoke. Keywords : Cigarette, Islamic Boarding School, Santri, Economy, Daily Money